A Rare Report of Heavy-Metal-Associated Hemodialysis-Dependent Chronic Kidney Disease Secondary to Ayurvedic Medication. Issue 1 (June 2021) - Mahapatra, Himansu Sekhar; Bhattacharyya, Sutanay; Batra, Vineeta V.
Introduction: Heavy metals are a component of many traditional medications. However, they continue to be used for trivial causes. Chronic heavy metal exposure is an important but under-recognized cause of renal damage. We report to our knowledge the first case of a heavy-metal-associated chronic kidney disease secondary to Ayurvedic medication. Case Report: A 24-year-old with history of chronic Ayurvedic medication for altered bowel habits presented with neuromuscular symptoms and bilateral lower limb swelling and was found to have hypocalcemia and renal dysfunction. He was initiated on dialysis and underwent an uncomplicated renal biopsy which was suggestive of chronic glomerulosclerosis. In view of significant exposure to Ayurvedic medication, he underwent heavy metal screening in blood, urine, and renal biopsy tissue along with the Ayurvedic medication he had. His blood tested positive for cadmium, copper, and mercury along with same positive results in Ayurvedic medication. He underwent chelation with dimercaprol 250 mg iv for 7 days with blood samples testing negative repeatedly for the same heavy metal that tested positive earlier. However, in view of significant chronicity, he became dialysis dependent and was initiated on twice weekly hemodialysis. His persistent gastrointestinal symptoms were attributed to nonspecific colitis following a computed tomography of the abdomen and colonoscopy with biopsy. He responded to rifaximin and probiotics. Conclusion: Heavy metal exposure, secondary to chronic Ayurvedic medication intake, is an unrecognized cause of renal dysfunction. The use of such medications for trivial purposes is rampant, especially in developing countries like India. Delaying diagnosis can lead to permanent renal damage with patients eventually becoming dialysis dependent.